Analysis of the Press Law and the Authority of Local Journalists in Mining Issues in East Kalimantan - Nurliah Nurliah; Jaka Farih Agustian; Johantan Alfando Wikandana Sucipta; Adinda Rahmadhani; Aulia Lun Ananda Putri (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Indonesia is endowed with abundant natural resources (SDA); however, unsustainable exploitation has resulted in severe environmental consequences. East Kalimantan, as a major hub for the coal mining industry, faces significant challenges related to illegal mining, which is spread across 168 locations. The negative impacts extend beyond environmental degradation, leading to fatalities due to abandoned mining pits that were never reclaimed. In this context, mass media serves as a public watchdog through critical and in-depth reporting. However, local journalists encounter various challenges in covering mining issues, including pressure from capital owners, risks of criminalization, and limited access to resources. This study aims to analyze the implementation of the Press Law in supporting press freedom and the challenges local journalists face in exposing mining realities in East Kalimantan. A qualitative approach with literature review methods was employed. The study results indicate that although local media such as RRI, Kaltim Post, Kaltim Kece, and TVRI fulfill their supervisory role as mandated by the Press Law, pressure from mining companies and political interests often obstruct objective and balanced reporting. Therefore, strengthening regulations and legal protections for journalists is essential to ensure that they can carry out their journalistic duties professionally, transparently, and responsibly, in line with the principles of environmental journalism.